ITPKC single nucleotide polymorphism associated with the Kawasaki disease in a Taiwanese population. - Ho-Chang Kuo (Public Library of Science (PLoS), 2011)
Kawasaki disease (KD) is characterized by systemic vasculitis with unknown etiology. Previous studies from Japan indicated that a gene polymorphism of ITPKC (rs28493229) is responsible for susceptibility to KD. We collected DNA samples from 1,531 Taiwanese subjects (341 KD patients and 1,190 controls) for genotyping ITPKC. In this study, no significant association was noted for the ITPKC polymorphism (rs28493229) between the controls and KD patients, although the CC genotype was overrepresented. We further combined our data with previously published case/control KD studies in the Taiwanese population and performed a meta-analysis. A significant association between rs28493229 and KD was found (Odds Ratio:1.36, 95% Confidence Interval 1.12-1.66). Importantly, a significant association was obtained between rs28493229 and KD patients with aneurysm formation (P = 0.001, under the recessive model). Taken together, our results indicated that C-allele of ITPKC SNP rs28493229 is associated with the susceptibility and aneurysm formation in KD patients in a Taiwanese population.